Assessing Prokaryotic Benthic Communities in the Red Sea - Christopher A. Hempel; Larissa Frühe; Sofia Frappi; Elisa Laiolo; Kah Kheng Lim; Diego E. Rivera Rosas; Amal A. Bajaffer; Wajitha J. R. M. Sait; Alexandra Steckbauer; Taiba Alamoudi; Jacqueline V. Alva García; Shannon G. Klein; et al. (Environmental Microbiology, 2026)
Marine sediments host diverse benthic prokaryotic communities that are integral to global biogeochemical cycles. However, the spatial distribution and environmental drivers of these communities, particularly in unique environments like the Red Sea, remain largely underexplored. In this study, we examine benthic prokaryotic communities sampled during the Red Sea Decade Expedition (RSDE) using 16S rRNA gene sequencing across five major regions along the Red Sea's latitudinal gradient and three depth strata. Our findings reveal distinct biogeographical patterns shaped by depth, latitude, and oxygen availability, with clear shifts in microbial community composition across the epibenthic, mesobenthic and bathybenthic zones. Bathybenthic communities exhibited consistently low levels of OTU richness throughout the Red Sea, likely due to uniform niche environmental conditions at depth, while shallower communities showed higher OTU richness towards the Southern Red Sea. The southern region harboured higher relative abundances of Chloroflexi and reduced relative abundances of Proteobacteria and Acidobacteriota relative to the northern regions. Extreme environments, such as the Atlantis II brine pool, supported specialised microbial communities likely adapted to extreme conditions like hypersalinity. This study established a critical baseline for understanding the responses of marine microbial communities to climate change and their roles in biogeochemical processes.